Challenges for Pastoral Care in Times of COVID-19: Encounters, Contexts, Topics and Professional Needs – A Cross-Sectional Study - Haußmann, Annette D; Fritz, Birthe (Health and Social Care Chaplaincy, 2022)
During the COVID-19 pandemic, challenges have arisen in pastoral care as a result of physical distancing and an increase in social and mental distress. Daily burdens and their consequences have led to an increased need for pastoral support in various fields, for example, hospitals, schools and church congregations. The study analyzes n = 307 pastoral carers in Germany in spring 2020 at the end of the first lockdown. Encounters and media use, interprofessional cooperation, topics of communication and the needs of pastoral carers were assessed for different areas of pastoral care. Results show a drastic decline in face-to-face communication, with significant differences between the various fields of pastoral care. The use of media has increased significantly, with a preference for synchronous interaction via telephone and video. Topics of pastoral care varied from everyday hassles to existential concerns, also including spiritual needs and struggles. Social isolation, the need to just talk to someone and the need for comfort and hope were mentioned the most. During the pandemic, pastoral carers used various media and established new ways to enable encounters and maintain contact. In the future, new methods for enabling pastoral care must be developed, evaluated and reflected on.